A lei complementar no sistema constitucional tributário - Ribeiro, Luiz Antonio (2005)
The complementary law, was introduced in the brazilian constitutional system by the 1967 Constitution. Among other topics, the Constitution attributed to complementary law the role to broach the tax subject. In the 1988 Federal Constitution, the complementary law have got emphasis in the National Taxation System, about, fundamentally, two attributions: 1) As a national law will forward rules that must be followed for all the political entities giving, the resolution to authority conflicts, the constitutional restriction to the taxation system and, specially, the general tax laws. The complementary law, in this case, hasn t the role of create tax; 2) As a federal law, in accordance with the Constitutional law, will establish the Union s tax. Therefore, it is evident, that the Federal Constitution in force order clearly the situations that claim the complementary law in tax subject edition.